Diseño de un seguidor solar automático para un arreglo básico de paneles fotovoltaicos (2016)
This project aimed to design an automatic solar tracking two axes for an array of four solar panels. The design of a diagnosis and taking into account the efficiency of photovoltaic systems installed in Bogotá evaluation. Thus the design features and functional requirements parameters required by the process of increasing the efficiency of photovoltaic systems was chosen.